Comparison of UAV photograph-based and airborne lidar-based point clouds over forest from a forestry application perspective. Issue 8 (19th May 2017) - Thiel, Christian; Schmullius, Christiane
ABSTRACT: In this study, unmanned aerial vehicle (UAV) image (photograph)-based point clouds and products were compared to airborne lidar-based data and products over a forested area. The test site is located in Germany, 15 km southeast of Jena. A total area of approximately 175 ha was covered during a UAV flight campaign. For this study, a subset of 4 ha (200 m × 200 m) was defined. The UAV–lidar comparison was accomplished at three different data levels: (1) point-like level (raster of maxima), (2) surface level (canopy height models), and (3) tree level (detection rate). In general, a high match between lidar- and UAV-based data/products was observed. The UAV data exhibits more details which are of particular importance for the detection of small trees. While using lidar data, 45 out of 205 trees were not detected, however only 14 trees were missed out when UAV data was used.